2013
DOI: 10.3389/fpsyg.2013.00952
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy-related traits and the use of reward and social information: a computational approach

Abstract: Psychopathy is often linked to disturbed reinforcement-guided adaptation of behavior in both clinical and non-clinical populations. Recent work suggests that these disturbances might be due to a deficit in actively using information to guide changes in behavior. However, how much information is actually used to guide behavior is difficult to observe directly. Therefore, we used a computational model to estimate the use of information during learning. Thirty-six female subjects were recruited based on their tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…They maintain that the findings on VM patients support their prediction that psychopaths will show impairments in response reversal task when the participants are aware of the task instructions, i.e. when the nature of the task promotes intentional, controlled behavior adaptation (Brazil et al, 2013a, p. E14; see also Brazil et al, 2013b). From this we can infer that VM patients and psychopaths are similar with regard to instrumental learning tasks because they are aware of the task requirements and instructions.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…They maintain that the findings on VM patients support their prediction that psychopaths will show impairments in response reversal task when the participants are aware of the task instructions, i.e. when the nature of the task promotes intentional, controlled behavior adaptation (Brazil et al, 2013a, p. E14; see also Brazil et al, 2013b). From this we can infer that VM patients and psychopaths are similar with regard to instrumental learning tasks because they are aware of the task requirements and instructions.…”
supporting
confidence: 55%
“…However, Brazil and colleagues (Brazil et al, 2013a(Brazil et al, , 2013b do not provide evidence for the conclusion (nor that seems to be in their focus) that psychopaths are aware of the relevant information when solving the task and do not respond to it as if they are subject to some motivational or motor-executive problems. They maintain that the findings on VM patients support their prediction that psychopaths will show impairments in response reversal task when the participants are aware of the task instructions, i.e.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Consistent with the hypothesis that social learning is 40 special, studies have demonstrated that social and individual learning are at least partially 41 dissociable. Behrens and colleagues 8 demonstrated activity relating to social and individual learning 42 in dissociable neural pathways, and a number of studies have found correlations between 43 personality traits and social, but not individual, learning [9][10][11] . 44 45 Studies, such as those mentioned above, that have dissociated social and individual learning have 46 typically used a single task wherein both social and individual learning happen concurrently.…”
mentioning
confidence: 99%